1975
DOI: 10.1017/s0016672300015391
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different selection intensities on selection response in egg-laying ofTribolium castaneum

Abstract: SUMMARYAn experiment was carried out to test the effect of varying selection intensity on the response to individual selection with a fixed number of individuals scored per generation. The selected trait was egg laying of virgin females of Tribolium castaneum scored from the 7th to the 1 lth day after adult emergence. Five different selected proportions of females were considered (5, 10, 20, 33 and 50%) and each treatment was represented by two replicate lines. Control lines were maintained throughout the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…S ilvela et al (1989) also indicated that total response to selection increased with larger selection intensities; when the population size was small, total response in lines with 5% selection intensity was almost twice that in lines with 17% selection intensity; the same was true with the high population size. In addition, these results agree with those of R uano et al (1975), showing that the 5% and 10% selection intensities had a larger response in the initial generations than the 20%, 33%, and 50% selection intensities.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…S ilvela et al (1989) also indicated that total response to selection increased with larger selection intensities; when the population size was small, total response in lines with 5% selection intensity was almost twice that in lines with 17% selection intensity; the same was true with the high population size. In addition, these results agree with those of R uano et al (1975), showing that the 5% and 10% selection intensities had a larger response in the initial generations than the 20%, 33%, and 50% selection intensities.…”
Section: Discussionsupporting
confidence: 88%
“…C layton et al (1957) and F rankham (1977) considered individual selection for abdominal bristle score in Drosophila the first experiment studied three different intensities (20, 27, 40, or 80%) with the same number of parents (20), whereas the second experiment compared three selection intensities (10, 20, or 40%). R uano et al (1975) analysed the effect of five different intensities (5, 10, 20, 33, or 50%) on selection response in egg laying in Tribolium. In general, the lines selected at the lowest proportions led to the largest initial responses.…”
Section: Introductionmentioning
confidence: 99%
“…Similar regular patterns were observed in a Tribolium egg production selection experiment (i.e. a character closely related to fitness) initiated from a cage population (Ruano, Orozco & Lopez-Fanjul, 1975) and in a selection experiment of cannon-bone length in Scottish blackface sheep (Atkins & Thompson, 1986). In the latter case, Atkins & Thompson showed that the response closely matched the predicted response of an 'infinitesimal model' which incorporated the effect of disequilibrium on the additive variance (Bulmer, 1980 ch.…”
Section: (I) Mutation-stabilizing Selection Balancementioning
confidence: 55%
“…Both mean and variances of virgin female egg laying were higher at 33°C. Orozco and Bell (l974a); (c) Ruano, Orozco and López-Fanjul (1975); (d) Orozco (1976b).…”
Section: Results (I) the Base Populationmentioning
confidence: 99%